Experimental Evidence on Taxpayer Reporting Under Uncertainty. - Beck, Paul J.; Davis, Jon S.; Jung, Woon-Oh (The Accounting Review, 1991)
The article reports on experimental tests of the effects of income uncertainty and other economic factors based on tax reporting models. Tax law complexity and ambiguity may result in uncertainty about taxable income and are of concern to policy-making bodies such as the ABA, the AICPA and the IRS. Hypotheses were tested regarding the effects of changes in the uncertainty level, tax rate, penalty rate, and audit probability on reported taxable income. In addition, the explanatory power of the models was evaluated by comparing the taxable income reported by the subjects with model-based predictions. Subjects were endowed with a fictitious currency and were given a range of possible post-audit taxable incomes from which to report. A proportional tax was paid on reported income and, in the event of an audit, a monetary penalty was imposed when the actual taxable income was greater than the amount reported. Incentives were provided by making the subjects' post-experimental remuneration a function of the after-tax income retained from each experimental trial.